Algal extracellular organic matter mediated photocatalytic degradation of estrogens - Wu, Pei-Hsun; Yeh, Hsin-Yi; Chou, Pei-Hsin; Hsiao, Wen-Wei; Yu, Chang-Ping (Ecotoxicology and environmental safety, 2021)
Estrogens are among the most concerned emerging contaminants in the wastewater treatment effluent due to their sexual disruption in aquatic wildlife. The use of microalgae for secondary wastewater effluent polishing is a promising approach due to the economic benefit and value-added products. In this study, three microalgae species, including Selenastrum capricornutum, Scenedesmus quadricauda and Chlorella vulgaris were selected to conduct batch experiments to examine important mechanisms, especially the role of algal extracellular organic matter (AEOM) on two selected estrogens (17β-estradiol, E2 and 17α-ethynylestradiol, EE2) removal. Results showed that estrogens could not be significantly degraded under visible light irradiation and adsorption of estrogens by microalgae was negligible. All three living microalgae cultures have ability to remove E2 and EE2, and Selenastrum capricornutum showed the highest E2 and EE2 removal efficiency of 91% and 83%, respectively, corresponding to the reduction of predicted estrogenic activity of 86%. AEOM from three microalgae cultures could induce photodegradation of estrogens, and AEOM from Selenastrum capricornutum and Chlorella vulgaris achieved 100% of E2 and EE2 removal under visible light irradiation. Fluorescence excitation–emission matrix spectroscopy identified humic/fulvic-like substances in AEOM from three microalgae cultures, which might be responsible for inducing the indirect photolysis of E2 and EE2. Therefore, in the living microalgae cultures, the major estrogens removal mechanisms should include biotransformation as well as AEOM meditated photocatalytic degradation. Since removal rates through photodegradation could be faster than biotransformation, the AEOM mediated photocatalytic degradation can play a potential role to remove emerging contaminants when using microalgae technology for wastewater effluent treatment. •S. capricornutum, C. vulgaris, and S. quadricauda were shown to degrade estrogens.•AEOM produced from microalgae could induce indirect photolysis of E2 and EE2.•EEM showed AEOM contained photosensitizing substances to induce photocatalytic degradation.•AEOM mediated indirect photolysis should be an important mechanism for estrogen removal by microalgae.